1963
DOI: 10.1152/ajplegacy.1963.204.4.655
|View full text |Cite
|
Sign up to set email alerts
|

Clearance rate in relation to agglutinins for gelatin-stabilized colloid in the rat

Abstract: Intravascular clearance rates of gelatin-stabilized gold were compared with circulating titers of gelatin agglutinins in rats at increasing time intervals after blockading injections of gelatin-stabilized gold and S. marcescens endotoxin. The degree and duration of reticuloendothelial system (RES) blockade against the homologous colloid were directly related to the circulating levels of gelatin agglutinins. In contrast, plasma agglutinins were not decreased in endotoxin-induced blockade against the gelatin-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1965
1965
1984
1984

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The majority of such investigations have concluded that reticuloendothellal system (RES) blockade is the result of saturation of the phagocytic capacity of the system (2)(3)(4), or saturation of clones of phagocytic cells which remove the specific particles under study (5). However, recent observations have suggested that RES blockade may be caused by depletion of specific serum opsonins by the preliminary blockading injection (6)(7)(8). The current experiments were undertaken to resolve these conflicting views.…”
mentioning
confidence: 99%
“…The majority of such investigations have concluded that reticuloendothellal system (RES) blockade is the result of saturation of the phagocytic capacity of the system (2)(3)(4), or saturation of clones of phagocytic cells which remove the specific particles under study (5). However, recent observations have suggested that RES blockade may be caused by depletion of specific serum opsonins by the preliminary blockading injection (6)(7)(8). The current experiments were undertaken to resolve these conflicting views.…”
mentioning
confidence: 99%
“…Moreover, this same author has reported that the degree and duration of reticuloeudothelial blockade to gelatin-stabilized colloidal gold induced by the same colloid was directly related to the circulating level of gelatin agglutinins and he suggested that opsonins rather than saturation of the phagocytic cell provided the limiting factor in the clearance rates. This is particularly interesting in relation to the present study on serum factors and carbon clearance when it is appreciated that the rate of clearance of colloidal carbon is itself decreased as the content of gelatin increases and that with increasing gelatin in the carbon preparation there is an exponential prolongation in the duration of inhibition to a given albumin dose (15). Whether the factor that adsorbs onto barium sulfate is indeed a gelatin agglutinln or is some other component of serum is not apparent from the present study and must await further clarification.…”
Section: Discussionmentioning
confidence: 86%
“…The participation of a serum factor in intravascular clearance has been suggested by several authors. Thus clearance rates have been related to changes in gamma-globulin (22) and in serum titers of complement (5) and antibody (15,23). Although studies relating clearance to antibody or complement usually refer to bacterial clearances, there is some evidence that serum proteins may also participate in the clearance of inert colloids as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations